With fire & sword : the battle of Bunker Hill and the beginning of the American Revolution - Nelson, James L. (New York : Thomas Dunne Books/St. Martin's Press, 2011)
Chronicles the events of the Battle of Bunker Hill and the beginning of the American Revolution, describing key figures from both sides, and how the battle's outcome influence British strategy throughout the course of the conflict.
Part I : From resistance to rebellion. The Lexington alarm ; Dr. Joseph Warren ; "The butchering hands of an inhuman soldiery" ; Weed of slavery ; Gage's return ; The loyal and orderly people ; A well-digested plan -- Part II : Prelude to war. From the Penn to the sword ; Officers and men ; The Massachusetts Army ; Three generals ; The siege of Boston -- Part III : The Battle of Bunker Hill. Charlestown Heights ; First light ; Redcoats and bluejackets ; The Battle of Bunker Hill ; Attack and repulse ; "We are all wrong at the head."
Includes bibliographical references (pages 321-351) and index.
Keywords: War -- Causes; Bunker Hill, Battle of, Boston, Mass., 1775.; Boston (Mass.) -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Causes; Massachusetts -- Boston; United States; 1775-1783; History; Nonfiction